Desalinization effect of simulated cut‐soiler‐based residue filled preferential shallow subsurface drainage: Improvement of physiology and yield of rain‐fed pearl millet in saline semiarid regions. (10th May 2022) - Neha,; Yadav, Gajender; Yadav, Rajender Kumar; Kumar, Ashwani; Rai, Arvind K.; Sehwag, Meena; Onishi, Junya; Omori, Keisuke; Sharma, Parbodh Chander
Abstract: Soil salinity is a major soil degradation problem that limits agricultural production. The cut‐soiler constructed preferential shallow subsurface drainage (PSSD) method is a promising salinity management technology for small‐scale application and adoption in drylands. This study assessed the effectiveness of rice residue‐filled PSSD in managing soil salinity and its effect on the physiology and yield of pearl millet. The cut‐soiler simulated drains were constructed manually in semi‐controlled lysimeter. A double replicated, split–spilt plot experiment, comprising with and without cut‐soiler drainage (main‐plot), two soil types (sub‐plot) and three irrigation water salinity (4, 8, 12 dS m −1 ) (sub‐sub plot) were conducted during 2019–2020. The cut‐soiler PSSD reduced ~60% soil salinity after 2 years. The PSSD reduced soil salinity by 23.28 and 41.46% in April 2019 and April 2020 (before pearl millet sowing). This reduction was 32.24 and 46.23% in October 2019 and 2020 (at harvest). Cut‐soiler drainage (PSSD) areas recorded lower soil moisture (%) indicated greater outflow of water and salinity. The salinity Inhibition efficiency increased upto 2 years of construction and then decline. The pearl millet grain and biological yields were improved by 23.54 and 12.64%, respectively and a positive effect on plant water relations and physiology was observed. The cut‐soiler PSSD was found to enhance salt removal and reduce salt accumulation under saline water irrigation. These drains can be constructed in a single farm operation at individual farm levels. Therefore, it could be a potential alternative for soil salinity management in semi arid regions irrigated with saline groundwater.